Confronting Challenges to Enterotoxigenic Escherichia coli Vaccine Development - Fleckenstein, James M. (Frontiers in Tropical Diseases, 2021)
The enterotoxigenic Escherichia coli (ETEC) are a diverse and genetically plastic pathologic variant (pathovar) of E. coli defined by their production of heat-labile (LT) and heat-stable (ST) enterotoxins. These pathogens, which came to recognition more than four decades ago in patients presenting with severe cholera-like diarrhea, are now known to cause hundreds of millions of cases of symptomatic infection annually. Children in low-middle income regions of the world lacking access to clean water and basic sanitation are disproportionately affected by ETEC. In addition to acute diarrheal morbidity, these pathogens remain a significant cause of mortality in children under the age of five years and have also been linked repeatedly to sequelae of childhood malnutrition and growth stunting. Vaccines that could prevent ETEC infections therefore remain a high priority. Despite several decades of effort, a licensed vaccine that protects against the breadth of these pathogens remains an aspirational goal, and the underlying genetic plasticity of E. coli has posed a fundamental challenge to development of a vaccine that can encompass the complete antigenic spectrum of ETEC. Nevertheless, novel strategies that include toxoids, a more complete understanding of ETEC molecular pathogenesis, structural details of target immunogens, and the discovery of more highly conserved antigens essential for virulence should accelerate progress and make a broadly protective vaccine feasible.